Disaster Risk and Business Cycles - Gourio, François (American Economic Review, 2012)
Motivated by the evidence that risk premia are large and countercyclical, this paper studies a tractable real business cycle model with a small risk of economic disaster, such as the Great Depression. An increase in disaster risk leads to a decline of employment, output, investment, stock prices, and interest rates, and an increase in the expected return on risky assets. The model matches well data on quantities, asset prices, and particularly the relations between quantities and prices, suggesting that variation in aggregate risk plays a significant role in some business cycles. (JEL E13, E32, E44, G32)